Intestinal parasites in Meche community in relation to their socio-economic status - Dhakal, N.; Subedi, Janak Raj (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Intestinal parasites still establishes one of the important causes of public health problem in world, especially in developing countries like Nepal. The aim of the study is to determine the prevalence of intestinal parasites in Meche community of Jalthal Village Development Committee of Jhapa district in relation to their socio-economic status. Material and Methods: Study was carried out during June to July 2017 in Meche community of Jalthal Village Development Committee of Jhapa district. A total of 150 human stool samples were randomly collected and examined using direct smear and concentration methods (sedimentation and flotation technique). Results: Among total samples the prevalence of intestinal parasites in Meche community was 27.33%. Prevalence rate in females were higher 32.47% than in males 21.91%. There was no significant difference in the distribution of parasites between male and female (χ2=1.6022, df=1, p value=0.2056). The prevalence of the parasites was maximum in the age group 21- 40 years (47.22%). Altogether 5 species of the intestinal parasites were detected. Among them Ascaris lumbricoides (19.33%) topped the list followed by Taenia solium (2.67%), Hookworm (2.67%), Entamoeba coli (2.67%) and Trichuris trichiura (2%). Conclusion: The high prevalence of infection in community seems directly related to un-hygienic living condition, unsafe drinking water, unhygienic food, lack of health education, poor sanitary condition and low socio-economic status help to increase the burden of the infection in the community.